2013
DOI: 10.1007/s13105-013-0275-2
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine and taurine treatments decreased oxidative stress and tissue damage induced by d-galactose in rat liver

Abstract: D-galactose (GAL) causes aging-related changes and oxidative stress in the organism. We investigated the effect of carnosine (CAR) or taurine (TAU), having antioxidant effects, on hepatic injury and oxidative stress in GAL-treated rats. Rats received GAL (300 mg/kg; s.c.; 5 days/week) alone or together with CAR (250 mg/kg/daily; i.p.; 5 days/week) or TAU (2.5 % w/w; in rat chow) for 2 months. Serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities and hepatic malondialdehyde (MDA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 44 publications
5
27
0
Order By: Relevance
“…In the present study, dietary supplementation with carnosine significantly increased the activities of T‐AOC, GSH‐Px and T‐SOD in thigh muscle. Similarly, previous studies have found that carnosine supplementation increased the activities of T‐SOD and GSH‐Px in skeletal muscle of finishing pigs, elevated GSH‐Px activity in the liver and kidney of diabetic mice and decreased pro‐oxidant status induced by d ‐galactose in the liver of rats . The antioxidant action of carnosine mainly depends on chelating divalent metal ions and scavenging free radicals .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In the present study, dietary supplementation with carnosine significantly increased the activities of T‐AOC, GSH‐Px and T‐SOD in thigh muscle. Similarly, previous studies have found that carnosine supplementation increased the activities of T‐SOD and GSH‐Px in skeletal muscle of finishing pigs, elevated GSH‐Px activity in the liver and kidney of diabetic mice and decreased pro‐oxidant status induced by d ‐galactose in the liver of rats . The antioxidant action of carnosine mainly depends on chelating divalent metal ions and scavenging free radicals .…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, previous studies have found that carnosine supplementation increased the activities of T-SOD and GSH-Px in skeletal muscle of finishing pigs, 26 elevated GSH-Px activity in the liver and kidney of diabetic mice 28 and decreased pro-oxidant status induced by D-galactose in the liver of rats. 30 The antioxidant action of carnosine mainly depends on chelating divalent metal ions and scavenging free radicals. 31 It has been indicated that carnosine can form charge transfer complexes with superoxide free radicals; at the same time, L-histidine can remove hydrogen peroxide radicals.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the extent of oxidative stress caused by high salt, samples from HH7 and HH10 chick embryos or primary cardiomyocytes were homogenized and analyzed for SOD (superoxide dismutase), GSH‐Px (glutathione peroxidase), and MDA (malondialdehyde) (Kalaz et al, ). The protein content of the chick embryos or primary cardiomyocytes was performed as previously reported (Zhang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Galactose treatment was reported to cause increases in lipid peroxides and PC levels and decreases in antioxidant enzyme activities in serum and tissues like liver and brain, together with histopathological changes and progressive deterioration in learning and memory capacity in rodents (Aydın et al., ; Han, Lin, Lee, Liang, & Hou, ; Kalaz et al., ; Xiong et al., ). In addition, some investigators have detected that AGE levels were increased in serum, liver and brain tissues of GAL‐treated rats (Han et al., ; Song et al., ; Xiong et al., ; Zhou et al., ).…”
Section: Discussionmentioning
confidence: 99%